Robot leadership–Investigating human perceptions and reactions towards social robots showing leadership behaviors - Cichor, Jakub Edward; Hubner-Benz, Sylvia; Benz, Tobias; Emmerling, Franziska; Peus, Claudia (PLOS ONE)
Human-robot interaction research has shown that social robots can interact with humans in complex social situations and display leadership-related behaviors. Therefore, social robots could be able to take on leadership roles. The aim of our study was to investigate human followers’ perceptions and reactions towards robot leadership behavior, and differences based on the robot’s displayed leadership style. We implemented a robot to show either a transformational or a transactional leadership style in its speech and its movements. We presented the robot to university and executive MBA students (N = 29) and subsequently conducted semi-structured interviews and group discussions. The results of explorative coding indicated that participants differed in their perceptions and reactions based on the robot’s leadership style and based on their assumptions about robots in general. We observed that participants quickly imagined either a utopia or worried about a dystopia, depending on the robot’s leadership style and their assumptions, and that a subsequent reflection led to more nuanced views. We discuss the implications and recommendations for human-robot interaction and leadership research.
Keywords: Multidisciplinary

The association of chronotype and social jet lag with body composition in German students: The role of physical activity behaviour and the impact of the pandemic lockdown - Krueger, Betina; Stutz, Bianca; Jankovic, Nicole; Alexy, Ute; Kilanowski, Anna; Libuda, Lars; Buyken, Anette E. (PLOS ONE)
Young adults with a later chronotype are vulnerable for a discrepancy in sleep rhythm between work- and free days, called social jet lag (SJL). This study analysed (i) chronotype/SJL association with visceral fat/skeletal muscle mass, (ii) the attribution to physical activity behaviour, and (iii) chronotype-specific changes in physical activity behaviour in young adults during the Covid-19 pandemic lockdown. Chronotype and SJL were derived from the Munich-Chrono-Type-Questionnaire in 320 German students (age 18–25 years) from September 2019 to January 2020, 156 of these participated in an online follow-up survey in June 2020. Body composition was assessed by bioimpedance analysis at baseline. Multivariable linear regression analyses were used to relate chronotype/SJL to body composition; the contribution of self-reported physical activity was tested by mediation analysis. At baseline, a later chronotype and a larger SJL were associated with a higher visceral fat mass (P<0.05), this relation was notably mediated by the attention to physical activity (P<0.05). Chronotype (P = 0.02) but not SJL (P = 0.87) was inversely associated with skeletal muscle mass. During the pandemic lockdown, chronotype hardly changed, but SJL was reduced. Timing and physical activity behaviour remained in most participants and changes were unrelated to chronotype (all P>0.07). A later chronotype/higher SJL may increase the risk of a higher visceral fat mass even in this relatively healthy sample, which may be partly due to their physical activity behaviour. Despite a reduction in SJL during the pandemic lockdown, later chronotypes did not change their physical activity behaviour more than earlier chronotypes.
Keywords: Multidisciplinary

Circularly polarized electroluminescence from a single-crystal organic microcavity light-emitting diode based on photonic spin-orbit interactions - Jia, Jichao; Cao, Xue; Ma, Xuekai; De, Jianbo; Yao, Jiannian; Schumacher, Stefan; Liao, Qing; Fu, Hongbing (Nature Communications)
Keywords: General Physics and Astronomy; General Biochemistry; Genetics and Molecular Biology; General Chemistry; Multidisciplinary

Dynamic control of hybrid grafted perfect vector vortex beams - Ahmed, Hammad; Ansari, Muhammad Afnan; Li, Yan; Zentgraf, Thomas; Mehmood, Muhammad Qasim; Chen, Xianzhong (Nature Communications)
Perfect vector vortex beams (PVVBs) have attracted considerable interest due to their peculiar optical features. PVVBs are typically generated through the superposition of perfect vortex beams, which suffer from the limited number of topological charges (TCs). Furthermore, dynamic control of PVVBs is desirable and has not been reported. We propose and experimentally demonstrate hybrid grafted perfect vector vortex beams (GPVVBs) and their dynamic control. Hybrid GPVVBs are generated through the superposition of grafted perfect vortex beams with a multifunctional metasurface. The generated hybrid GPVVBs possess spatially variant rates of polarization change due to the involvement of more TCs. Each hybrid GPVVB includes different GPVVBs in the same beam, adding more design flexibility. Moreover, these beams are dynamically controlled with a rotating half waveplate. The generated dynamic GPVVBs may find applications in the fields where dynamic control is in high demand, including optical encryption, dense data communication, and multiple particle manipulation.
Keywords: General Physics and Astronomy; General Biochemistry; Genetics and Molecular Biology; General Chemistry; Multidisciplinary

Housing situations and local COVID-19 infection dynamics using small-area data - Freise, Diana; Schiele, Valentin; Schmitz, Hendrik (Scientific Reports)
Abstract Low socio-economic status is associated with higher SARS-CoV-2 incidences. In this paper we study whether this is a result of differences in (1) the frequency, (2) intensity, and/or (3) duration of local SARS-CoV-2 outbreaks depending on the local housing situations. So far, there is not clear evidence which of the three factors dominates. Using small-scale data from neighborhoods in the German city Essen and a flexible estimation approach which does not require prior knowledge about specific transmission characteristics of SARS-CoV-2, behavioral responses or other potential model parameters, we find evidence for the last of the three hypotheses. Outbreaks do not happen more often in less well-off areas or are more severe (in terms of the number of cases), but they last longer. This indicates that the socio-economic gradient in infection levels is at least in parts a result of a more sustained spread of infections in neighborhoods with worse housing conditions after local outbreaks and suggests that in case of an epidemic allocating scarce resources in containment measures to areas with poor housing conditions might have the greatest benefit.
Keywords: Multidisciplinary

Click me…! The influence of clickbait on user engagement in social media and the role of digital nudging - Jung, Anna-Katharina; Stieglitz, Stefan; Kissmer, Tobias; Mirbabaie, Milad; Kroll, Tobias (PLOS ONE)
Clickbait to make people click on a linked article is commonly used on social media. We analyze the impact of clickbait on user interaction on Facebook in the form of liking, sharing and commenting. For this, we use a data set of more than 4,400 Facebook posts from 10 different news sources to analyze how clickbait in post headlines and in post text influences user engagement. The results of our study revealed that certain features (e.g., unusual punctuation and common clickbait phrases) increase user interaction, whereas others decrease engagement with Facebook posts. We further use our results to discuss the potential role of digital nudging in the context of clickbait. Our results contribute to understanding and making use of the effect of different framings in social media.
Keywords: Multidisciplinary

Nonlinear down-conversion in a single quantum dot - Jonas, B.; Heinze, Dirk Florian; Schöll, E.; Kallert, P.; Langer, T.; Krehs, S.; Widhalm, A.; Jöns, Klaus; Reuter, Dirk; Schumacher, Stefan; Zrenner, Artur (Nature Communications)
Abstract Tailored nanoscale quantum light sources, matching the specific needs of use cases, are crucial building blocks for photonic quantum technologies. Several different approaches to realize solid-state quantum emitters with high performance have been pursued and different concepts for energy tuning have been established. However, the properties of the emitted photons are always defined by the individual quantum emitter and can therefore not be controlled with full flexibility. Here we introduce an all-optical nonlinear method to tailor and control the single photon emission. We demonstrate a laser-controlled down-conversion process from an excited state of a semiconductor quantum three-level system. Based on this concept, we realize energy tuning and polarization control of the single photon emission with a control-laser field. Our results mark an important step towards tailored single photon emission from a photonic quantum system based on quantum optical principles.
Keywords: General Physics and Astronomy; General Biochemistry; Genetics and Molecular Biology; General Chemistry; Multidisciplinary

Manipulating polariton condensates by Rashba-Dresselhaus coupling at room temperature - Li, Yao; Ma, Xuekai; Zhai, Xiaokun; Gao, Meini; Dai, Haitao; Schumacher, Stefan; Gao, Tingge (Nature Communications)
Keywords: General Physics and Astronomy; General Biochemistry; Genetics and Molecular Biology; General Chemistry; Multidisciplinary

Hydrogen bond dynamics of interfacial water molecules revealed from two-dimensional vibrational sum-frequency generation spectroscopy - Ojha, Deepak; Kühne, Thomas (Scientific Reports)
Abstract Vibrational sum-frequency generation (vSFG) spectroscopy allows the study of the structure and dynamics of interfacial systems. In the present work, we provide a simple recipe, based on a narrowband IR pump and broadband vSFG probe technique, to computationally obtain the two-dimensional vSFG spectrum of water molecules at the air–water interface. Using this technique, to study the time-dependent spectral evolution of hydrogen-bonded and free water molecules, we demonstrate that at the interface, the vibrational spectral dynamics of the free OH bond is faster than that of the bonded OH mode.
Keywords: Multidisciplinary

Artificial Neural Networks as Trial Wave Functions for Quantum Monte Carlo - Kessler, Jan; Calcavecchia, Francesco; Kühne, Thomas (Advanced Theory and Simulations)
Keywords: Multidisciplinary; Modeling and Simulation; Numerical Analysis; Statistics and Probability

How does spectator presence affect football? Home advantage remains in European top-class football matches played without spectators during the COVID-19 pandemic - Wunderlich, Fabian; Weigelt, Matthias; Rein, Robert; Memmert, Daniel (PLOS ONE)
The present paper investigates factors contributing to the home advantage, by using the exceptional opportunity to study professional football matches played in the absence of spectators due to the COVID-19 pandemic in 2020. More than 40,000 matches before and during the pandemic, including more than 1,000 professional matches without spectators across the main European football leagues, have been analyzed. Results support the notion of a crowd-induced referee bias as the increased sanctioning of away teams disappears in the absence of spectators with regard to fouls (p < .001), yellow cards (p < .001), and red cards (p < .05). Moreover, the match dominance of home teams decreases significantly as indicated by shots (p < .001) and shots on target (p < .01). In terms of the home advantage itself, surprisingly, only a non-significant decrease is found. While the present paper supports prior research with regard to a crowd-induced referee bias, spectators thus do not seem to be the main driving factor of the home advantage. Results from amateur football, being naturally played in absence of a crowd, provide further evidence that the home advantage is predominantly caused by factors not directly or indirectly attributable to a noteworthy number of spectators.
Keywords: Multidisciplinary

Low-field onset of Wannier-Stark localization in a polycrystalline hybrid organic inorganic perovskite - Berghoff, Daniel; Bühler, Johannes; Bonn, Mischa; Leitenstorfer, Alfred; Meier, Torsten; Kim, Heejae (Nature Communications)
Abstract Methylammonium lead iodide perovskite (MAPbI 3 ) is renowned for an impressive power conversion efficiency rise and cost-effective fabrication for photovoltaics. In this work, we demonstrate that polycrystalline MAPbI 3 s undergo drastic changes in optical properties at moderate field strengths with an ultrafast response time, via transient Wannier Stark localization. The distinct band structure of this material - the large lattice periodicity, the narrow electronic energy bandwidths, and the coincidence of these two along the same high-symmetry direction – enables relatively weak fields to bring this material into the Wannier Stark regime. Its polycrystalline nature is not detrimental to the optical switching performance of the material, since the least dispersive direction of the band structure dominates the contribution to the optical response, which favors low-cost fabrication. Together with the outstanding photophysical properties of MAPbI 3 , this finding highlights the great potential of this material in ultrafast light modulation and novel photonic applications.
Keywords: General Physics and Astronomy; General Biochemistry; Genetics and Molecular Biology; General Chemistry; Multidisciplinary

EEG‑derived brain graphs are reliable measures for exploring exercise‑induced changes in brain networks - Büchel, Daniel; Lehmann, Tim; Sandbakk, Øyvind; Baumeister, Jochen (Scientific Reports)
Keywords: Multidisciplinary

Unraveling the electrochemical and spectroscopic properties of neutral and negatively charged perylene tetraethylesters - Wiebeler, Christian; Vollbrecht, Joachim; Neuba, Adam; Kitzerow, Heinz-Siegfried; Schumacher, Stefan (Scientific Reports)
Abstract A detailed investigation of the energy levels of perylene-3,4,9,10-tetracarboxylic tetraethylester as a representative compound for the whole family of perylene esters was performed. It was revealed via electrochemical measurements that one oxidation and two reductions take place. The bandgaps determined via the electrochemical approach are in good agreement with the optical bandgap obtained from the absorption spectra via a Tauc plot. In addition, absorption spectra in dependence of the electrochemical potential were the basis for extensive quantum-chemical calculations of the neutral, monoanionic, and dianionic molecules. For this purpose, calculations based on density functional theory were compared with post-Hartree–Fock methods and the CAM-B3LYP functional proved to be the most reliable choice for the calculation of absorption spectra. Furthermore, spectral features found experimentally could be reproduced with vibronic calculations and allowed to understand their origins. In particular, the two lowest energy absorption bands of the anion are not caused by absorption of two distinct electronic states, which might have been expected from vertical excitation calculations, but both states exhibit a strong vibronic progression resulting in contributions to both bands.
Keywords: Multidisciplinary

Energy transfer within the hydrogen bonding network of water following resonant terahertz excitation - Elgabarty, Hossam; Kampfrath, Tobias; Bonthuis, Douwe Jan; Balos, Vasileios; Kaliannan, Naveen Kumar; Loche, Philip; Netz, Roland R.; Wolf, Martin; Kühne, Thomas; Sajadi, Mohsen (Science Advances)
Energy flow in the hydrogen bonding network of water is traced by resonant terahertz excitation and off-resonant optical probing.
Keywords: Multidisciplinary

Key activity descriptors of nickel-iron oxygen evolution electrocatalysts in the presence of alkali metal cations - Görlin, Mikaela; Halldin Stenlid, Joakim; Koroidov, Sergey; Wang, Hsin-Yi; Börner, Mia; Shipilin, Mikhail; Kalinko, Aleksandr; Murzin, Vadim; Safonova, Olga V.; Nachtegaal, Maarten; Uheida, Abdusalam; Dutta, Joydeep; et al. (Nature Communications)
Abstract Efficient oxygen evolution reaction (OER) electrocatalysts are pivotal for sustainable fuel production, where the Ni-Fe oxyhydroxide (OOH) is among the most active catalysts for alkaline OER. Electrolyte alkali metal cations have been shown to modify the activity and reaction intermediates, however, the exact mechanism is at question due to unexplained deviations from the cation size trend. Our X-ray absorption spectroelectrochemical results show that bigger cations shift the Ni 2+/(3+δ)+ redox peak and OER activity to lower potentials (however, with typical discrepancies), following the order CsOH > NaOH ≈ KOH > RbOH > LiOH. Here, we find that the OER activity follows the variations in electrolyte pH rather than a specific cation, which accounts for differences both in basicity of the alkali hydroxides and other contributing anomalies. Our density functional theory-derived reactivity descriptors confirm that cations impose negligible effect on the Lewis acidity of Ni, Fe, and O lattice sites, thus strengthening the conclusions of an indirect pH effect.
Keywords: General Physics and Astronomy; General Biochemistry; Genetics and Molecular Biology; General Chemistry; Multidisciplinary

Social cues can impact complex behavior unconsciously - Schütz, Christoph; Güldenpenning, Iris; Koester, Dirk; Schack, Thomas (Scientific Reports)
Abstract In three experiments, we investigated the effect of unconscious social priming on human behavior in a choice reaction time task. Photographs of a basketball player passing a ball to the left/right were used as target stimuli. Participants had to respond to the pass direction either by a whole-body (complex) response or a button-press (simple) response. Visually masked stimuli, showing both a task-relevant cue (pass direction) and a task-irrelevant, social cue (gaze direction), were used as primes. Subliminal social priming was found for kinematic (center of pressure) and chronometric measures (response times): gaze direction in the primes affected responses to the pass direction in the targets. The social priming effect diminished when gaze information was unhelpful or even detrimental to the task. Social priming of a complex behavior does not require awareness or intentionality, indicating automatic processing. Nevertheless, it can be controlled by top-down, strategic processes.
Keywords: Multidisciplinary

Enhancement of the local asymmetry in the hydrogen bond network of liquid water by an ultrafast electric field pulse - Elgabarty, Hossam; Kaliannan, Naveen Kaliannan; Kühne, Thomas (Scientific Reports)
Keywords: Multidisciplinary

Nonlinear integrated quantum electro-optic circuits - Luo, Kai-Hong; Brauner, Sebastian; Eigner, Christof; Sharapova, Polina; Ricken, Raimund; Meier, Torsten; Herrmann, Harald; Silberhorn, Christine (Science Advances)
An integrated chip with quantum state generation, active polarization manipulation, and precise time control is demonstrated.
Keywords: Multidisciplinary

Lateral association and elongation of vimentin intermediate filament proteins: A time-resolved light-scattering study - Lopez, Carlos G.; Saldanha, Oliva; Huber, Klaus; Köster, Sarah (Proceedings of the National Academy of Sciences)
Significance The hierarchical assembly pathway of the cytoskeletal protein vimentin may be responsible for the astonishing mechanical properties of the emerging filaments, such as high flexibility and extensibility, and thus play a key role in cellular mechanics. A two-step assembly mechanism, involving a lateral and a subsequent elongational step, has been established; however, the elongational step could not be followed in solution. Here, we show direct in situ observation and modeling of the elongation reaction of the filaments on the relevant length and time scales, using time-resolved, multiangle static and dynamic light scattering. We thus achieve sufficient spatio-temporal resolution without the need of labeling, staining, or adsorption to substrates.
Keywords: Multidisciplinary